(untitled) (REMUNOM, 2023)
COVID-19 had a major impact on healthcare, including in dentistry, with clinics and offices being temporarily closed, affecting the income of entrepreneurs in the sector. Given this scenario, entrepreneurship in dentistry can be an alternative for professionals to face the challenges of the market. The research seeks to understand the importance of entrepreneurship in dentistry in the post-pandemic period in Brazil, identify opportunities and challenges for entrepreneurs in the area and analyze the impact of the pandemic on the sector. The scientific literature already points to the importance of entrepreneurship in dentistry, allowing professionals to face the difficulties imposed by the market. The research will be carried out through a systematic review of the literature, with a quantitative analysis of data obtained from different databases. The research will seek to identify trends and opportunities related to entrepreneurship in dentistry and the challenges that entrepreneurs need to face and will assess how entrepreneurs in the area are adapting to this new scenario and what strategies they are adopting to overcome the challenges and take advantage of the opportunities that arise in this post-pandemic period. The survey results can be useful for governments and institutions that want to support and encourage entrepreneurship in the health area, especially in a period of economic recovery after the pandemic, as there is a lack of information about entrepreneurship in dentistry and this topic should be better explored by the literature in general.